Internet sebagai media masyarakat virtual: Inovasi aplikasi perpustakaan online berbasis mobile - Arin Krisdiana (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2021)
The internet will continue to develop along with the times, this also has an impact on the development of information technology as well as the needs of the community begin to change. Today's society has begun to create virtual communities according to their needs and has begun to switch to mobile-based online applications. This mobile-based online application is starting to become familiar to the virtual community, such as the gojek application, the halo doc application, and the online shopping application. Therefore this can be an innovation in the world of libraries. Libraries can build a mobile-based online application that can be accessed via Android which contains the world of libraries. The purpose of this research is to make innovations related to the needs of virtual communities in the form of mobile-based online library applications. This research method uses descriptive qualitative method through literature study, namely research based on literature study and analysis of the development of problems in society. The results of the research are in the form of designing mobile-based online library application layouts in the form of profiles and library visits throughout Indonesia, library design services, library management services, e-books, and consulting book recommendations and research sources, and talking with users and librarian.